Physiological, and genetic characterization of 2,4-D-resistant Palmer amaranth (Amaranthus palmeri S. Watson) and its management - Shyam, Chandrima (Kansas State University, 2021)
Palmer amaranth (Amaranthus palmeri S. Watson) is one of the topmost troublesome, C4 dioecious weeds in the US. Biological traits such as aggressive growth habits, prolific seed production, and the ability to withstand environmental stresses hinder control of this weed. Additionally, numerous Palmer amaranth populations across the US have been found to have evolved resistance to multiple herbicides. In 2018, a population of Palmer amaranth from a conservation tillage study from Riley County, Kansas was suspected to have evolved resistance to multiple herbicides including 2,4-dichlorophenoxyacetic acid (2,4-D) and was designated as Kansas Conservation Tillage Resistant (KCTR). 2,4-D, a synthetic auxin herbicide, is widely used for controlling broadleaf weeds in cereal crops. However, over-reliance on 2,4-D to control other herbicide-resistant weeds, along with the commercialization of 2,4-D-tolerant crop technology, has resulted in increased usage of this herbicide. The objectives of this dissertation were to 1) characterize the evolution of multiple herbicide resistance including 2,4-D in KCTR Palmer amaranth; 2) investigate the physiological mechanism of 2,4-D resistance in KCTR compared to two known susceptible Palmer amaranth populations i.e., Kansas Susceptible (KSS) and Mississippi Susceptible (MSS); 3) assess the genetic basis of 2,4-D resistance in KCTR; and 4) evaluate herbicide programs that can manage glyphosate-resistant Palmer amaranth in 2,4-D tolerant soybean. Experiments were conducted under either greenhouse or controlled growth chamber conditions. Standard herbicide dose-response, physiological, biochemical (using radiolabeled herbicides), breeding, and field experiments were designed and conducted. The results of these experiments found that KCTR Palmer amaranth had evolved resistance to six herbicide modes of action, including acetolactate synthase (ALS)-, photosystem II (PS II)-, 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS)-, 4-hydroxyphenylpyruvate dioxygenase (HPPD)-, protoporphyrinogen oxidase (PPO)- inhibitors, and synthetic auxins (2,4-D). Sequencing and analyses of genes coding for the herbicide targets indicated absence of all known mutations that confer resistance, except for EPSPS-inhibitor, with a massive amplification of EPSPS gene (up to 88 copies). Investigation of non-target site resistance mechanism(s) in KCTR confirmed the predominance of metabolic resistance to multiple herbicides mediated by either cytochrome P450 (P450) or glutathione S-transferase enzyme activity. Whole-plant dose-response analyses confirmed a 6- to 11- fold resistance to 2,4-D in KCTR compared to two susceptible populations (KSS or MSS). [¹⁴C] 2,4-D uptake and translocation studies indicated a 10% less and 3 times slower translocation of [¹⁴C] 2,4-D in KCTR compared to susceptible populations, while there was no difference in the amount of [¹⁴C] 2,4-D absorbed. However, KCTR plants metabolized [¹⁴C] 2,4-D much faster than the susceptible KSS and MSS, suggesting that enhanced metabolism bestows resistance to this herbicide in KCTR. Further, use of P450-inhibitor (e.g., malathion) indicated that the metabolism of 2,4-D in KCTR is mediated by P450 activity. Genetic analyses of F₁ and F₂ progenies, derived from crossing between KCTR and KSS, revealed that 2,4-D resistance in KCTR Palmer amaranth is an incompletely dominant, nuclear trait. Segregation of F₂ progenies did not follow the Mendelian single gene inheritance model (3:1), suggesting the involvement of multiple genes in mediating 2,4-D resistance in KCTR. Evaluation of herbicide programs for Palmer amaranth management in the field suggested that pre-emergence herbicides with residual activity followed by post-emergence application of either 2,4-D or glufosinate or 2,4-D and glufosinate can control glyphosate-resistant Palmer amaranth in 2,4-D-tolerant soybean. Overall, the outcome of this dissertation documents the first case of a six-way resistance in a single Palmer amaranth population and also for the first time characterizes the physiological and genetic basis of 2,4-D resistance in this weed. These findings will help in predicting and minimizing further evolution and spread of 2,4-D resistance in Palmer amaranth.
Keywords: Palmer amaranth; 2,4-D resistance; Metabolic resistance; Inheritance; Herbicide program evaluation